Composite catalyst bed layer and application thereof

By using a composite catalyst bed in the lightening process of heavy aromatic hydrocarbons, and using silicon-aluminum molecular sieves of different pore sizes to match the raw material molecular conversion reaction, the problems of high energy consumption, low resource utilization and reduced catalyst activity in the prior art are solved, and efficient lightweighting and high BTX selectivity are achieved.

CN119897148AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311398683.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The prior art has problems such as high energy consumption, low resource utilization and strict restrictions on the content of naphthalene in the lightening process of heavy aromatic hydrocarbons, resulting in reduced catalyst activity and coking inactivation.

Method used

The composite catalyst bed is used to match the molecular conversion reactions of different raw materials through silicon-aluminum molecular sieves of different pore sizes, including multiple layers of beds filled with catalysts. Each layer of catalyst independently contains silicon-aluminum molecular sieves, metal components and binders, and the pore structure and metal load of the molecular sieve are gradually adjusted according to the order of material contact.

Benefits of technology

Effectively utilize the naphthalene products in heavy aromatic hydrocarbons to improve resource utilization, significantly improve the conversion rate and BTX selectivity of lightweight reactions, and extend the stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004514522430000131
    Figure BDA0004514522430000131
  • Figure BDA0004514522430000161
    Figure BDA0004514522430000161
Patent Text Reader

Abstract

The invention discloses a composite catalyst bed layer and an application thereof, and particularly relates to an application in increasing the yield of light C6-C8 aromatic hydrocarbons by using heavy aromatic hydrocarbons. The composite catalyst bed layer comprises a plurality of bed layers filled with catalysts, the catalysts respectively and independently comprise silicon-aluminum molecular sieves, metal components and optional binders, and pore structures of the silicon-aluminum molecular sieves in the catalysts of all the bed layers are gradually reduced according to the sequence of contact with materials. The composite catalyst bed can be used for lightening heavy aromatic hydrocarbons, and especially can be used for lightening C9 + A aromatic hydrocarbons containing naphthalene and / or derivatives thereof, molecular sieves with different pore diameters are matched with different raw material molecular conversion reactions, naphthalene and / or derivatives thereof in heavy aromatic hydrocarbons can be effectively utilized, the utilization rate of heavy aromatic hydrocarbon resources is improved, and the cost is reduced. And the conversion rate of the heavy aromatics lightening reaction and the selectivity of the target product BTX can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a composite catalyst bed and application thereof, in particular to application in increasing the production of light C6-C8 aromatics from heavy aromatics. Background Art

[0002] Heavy aromatics are byproducts of petroleum processing. People usually refer to C9A and C10Aromatics as 10 A) and heavy aromatic hydrocarbons with carbon 11 or above (C 11 + A) Collectively referred to as heavy aromatics. Petroleum heavy aromatics mainly come from by-products of catalytic cracking, catalytic reforming and naphtha steam cracking units in refineries. The structural composition of heavy aromatics is very complex. In addition to containing more methyl, ethyl and propyl groups, it also contains more polycyclic aromatic hydrocarbons. With the development of heavy crude oil, the resources of by-product heavy aromatics will increase.

[0003] Aromatics complex is a chemical plant that produces BTX (benzene, toluene and xylene) light aromatics through catalytic reforming, aromatics extraction, disproportionation / transalkylation, isomerization, adsorption separation and other processes. The heavy aromatics produced by the catalytic reforming unit mainly contain monocyclic aromatics, and also contain about 3-5% polycyclic aromatics. Most of the reformed heavy aromatics can be converted into xylene through heavy aromatic lightening or disproportionation and transalkylation units. For example, TAC9 developed by UOP is suitable for processing pure C9A / C 10 A aromatics, and TA series alkyl transfer catalysts are suitable for processing raw materials containing a certain amount of monocyclic heavy aromatics, but the above catalysts have certain restrictions on the content of condensed aromatics in the raw materials, and the reformed heavy aromatics need to be separated to remove the naphthalene components before use. There are problems in the process such as high energy consumption for heavy aromatic separation and low utilization rate of heavy aromatic resources. Further reducing the energy and material consumption of the device and improving the utilization rate of inferior heavy aromatic raw materials are the future development trends of aromatics devices. However, the higher the content of heavy aromatics with carbon ten or above in the reaction raw materials, especially the higher the content of naphthalene, the lower the activity of the catalyst, and the easier it is to coke and deactivate. Therefore, the traditional alkyl transfer process has strict restrictions on the content of naphthalene in the reaction raw materials. At present, the disproportionation and alkyl transfer units are for C9 + The utilization of heavy aromatics is mainly focused on C9A and some C 10 The utilization of A, while naphthalene and C 11 + A is discharged from the bottom of the heavy aromatics tower because it cannot be effectively utilized. It is generally used to blend diesel and fuel. In recent years, the light utilization of naphthalene compounds has gradually been developed by scholars. It needs to be carried out under the action of metal and acid bifunctional catalysts to produce light aromatics through partial ring opening hydrogenation and hydrocracking processes. Precious metals such as platinum and palladium have been reported as selective ring opening metal compounds.

[0004] WO2019177961A1 (2019-3-11) Saudi Arabian Oil Company discloses a method for preparing BTX compounds of benzene, toluene and xylene. The process feeds the reforming product into a reactor containing a composite zeolite catalyst. The composite zeolite catalyst includes a mixture of nano beta and ZSM-5. Nano beta, ZSM-5 or both include one or more impregnated metals, 0.25 to 0.55wt.% Re. The main feature of this patent is the limitation of the nano beta particle size, which is between 10-40nm, the external specific surface area is higher than 150m2 / g, and the silicon-aluminum ratio is between 6-12. With the hydrogenation of the metal, the molecular sieve can be used for both transalkylation and dealkylation processes. The presence of the nano beta molecular sieve leads to an increase in the external specific surface of the catalyst, which can effectively improve the transalkylation conversion rate and dealkylation performance of heavy aromatics. The catalyst can process high C9+A raw materials and improve the yield of mixed xylenes and catalyst stability. ExxonMobil Chemical Patent Company US20200031740A1 discloses a new process for converting C9 and above heavy aromatics into benzene, toluene and xylene. The patent uses two catalysts containing active components such as zeolite, a first metal and / or a second metal and a binder, namely a first catalyst and a second catalyst, to effectively improve the yield of benzene, toluene and xylene. The process mainly combines the dealkylation and transalkylation processes, and under hydrogen conditions, C9 and above heavy aromatics are lightened using a sulfurized bifunctional catalyst. In this process, C9 and above heavy aromatics are first converted into benzene, toluene and xylene and low-carbon alkanes C2 by dealkylation. + The remaining C9 and above heavy aromatics are further transalkylated with the generated benzene and toluene to generate xylene. Different from the previous process, this process uses different bed catalysts or physically mixed two catalysts to convert C9 + Aromatics are lightened into benzene, toluene and xylene. The above reaction system is mainly connected in series through multiple reactors, which increases the investment in equipment and the complexity of the process. Summary of the invention

[0005] In order to overcome the problems existing in the prior art, the present invention provides a composite catalyst bed and a preparation method and application thereof. The composite catalyst bed utilizes molecular sieves of different pore sizes to match different raw material molecular conversion reactions, which can effectively utilize naphthalene compounds in heavy aromatics and improve the utilization rate of heavy aromatics resources.

[0006] One aspect of the present invention is to provide a composite catalyst bed, which includes multiple layers of beds filled with catalysts, wherein the catalysts independently include silica-alumina molecular sieves, metal components and optional binders, and the pore structure of the silica-alumina molecular sieves in each bed catalyst gradually decreases in the order of contact with the material.

[0007] The binder is selected from at least one of alumina, aluminum sol, pseudo-boehmite, and silica sol. Preferably, in each bed of the catalyst, based on the total weight of the silica-alumina molecular sieve and the binder as 100wt%, the silica-alumina molecular sieve is independently 10-85wt%, and the binder is independently 5-80wt%.

[0008] The metal components are each independently selected from at least one of Group IB, Group IIB, Group VIB, Group VIII and Group VIIB elements, preferably at least one of Ni, Mo, Re, Pd, Co, Rh, Ru, Ir, Cr, Pt and Zn. More preferably, the loading amount of the metal components in each bed catalyst is each independently 0.01 to 25 wt%.

[0009] According to the order of contact with the material, the number of T atoms in the skeleton of the largest ring structure on the silica-alumina molecular sieve in each bed catalyst gradually decreases (preferably in the range of 20 to 6, more preferably in the range of 18 to 9);

[0010] More preferably, the silicon-aluminum molecular sieve is selected from at least one of AET molecular sieve, ETR molecular sieve, ZEO-1 molecular sieve, UTD-1F molecular sieve, β zeolite molecular sieve, mordenite molecular sieve, ZSM-12 molecular sieve, Y molecular sieve, MCM-22 molecular sieve, ITQ-1 molecular sieve, ITQ-24 molecular sieve, ITQ-32 molecular sieve, AFR molecular sieve, ZSM-22 molecular sieve, ZSM-23 molecular sieve, ZSM-5 molecular sieve, EU-1 molecular sieve, ITQ-13 molecular sieve, NU-87 molecular sieve, ZSM-34 molecular sieve and ZSM-11 molecular sieve.

[0011] According to the order of contact with the material, the aluminum content and / or acid amount of the silica-alumina molecular sieve in the catalyst of each bed layer gradually increases; preferably, the aluminum content and / or acid amount of the silica-alumina molecular sieve in the catalyst of each bed layer is 10 to 500 μmol pydg according to the order of contact with the material. -1 (Preferably 20 to 450 μmol pydg -1 ) range gradually increases.

[0012] The composite catalyst bed comprises three or more layers filled with catalyst, preferably 3 to 10 layers, more preferably 3 to 6 layers.

[0013] The composite catalyst bed comprises three layers. In the order of contact with the material, the number of T atoms in the skeleton of the largest ring structure of the silicon-aluminum molecular sieve in the catalyst of the first layer is 14 to 18; and / or, the number of T atoms in the skeleton of the largest ring structure of the silicon-aluminum molecular sieve in the catalyst of the second layer is 11 to 12; and / or, the number of T atoms in the skeleton of the largest ring structure of the silicon-aluminum molecular sieve in the catalyst of the third layer is 9 to 10.

[0014] The composite catalyst bed comprises three layers. In the order of contact with the material, the silicon-aluminum molecules in the catalyst of the first bed are selected from at least one of AET molecular sieve, ETR molecular sieve, ZEO-1 molecular sieve, and UTD-1F molecular sieve; and / or, the silicon-aluminum molecules in the catalyst of the second bed are selected from at least one of β zeolite molecular sieve, mordenite molecular sieve, ZSM-12 molecular sieve, Y molecular sieve, MCM-22 molecular sieve, ITQ-1 molecular sieve, ITQ-24 molecular sieve, ITQ-32 molecular sieve, and AFR molecular sieve; and / or, the silicon-aluminum molecules in the catalyst of the third bed are selected from at least one of ZSM-22 molecular sieve, ZSM-23 molecular sieve, ZSM-5 molecular sieve, EU-1 molecular sieve, ITQ-13 molecular sieve, NU-87 molecular sieve, ZSM-34 molecular sieve, and ZSM-11 molecular sieve.

[0015] The composite catalyst bed comprises three layers. According to the order of contact with the material, the acid content of the silica-alumina molecular sieve in the catalyst of the first bed is 20-200 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the second bed is 200 to 300 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the third bed is 320 to 450 μmol pydg -1 .

[0016] The second aspect of the present invention is to provide the application of the composite catalyst bed, preferably in the lightening of heavy aromatics.

[0017] The third aspect of the present invention is to provide a method for lightening heavy aromatic hydrocarbons, comprising: under hydrogen conditions, the heavy aromatic hydrocarbon raw material is contacted and reacted with the composite catalyst bed.

[0018] The heavy aromatic hydrocarbon raw material is C9 + A aromatic hydrocarbon, preferably, wherein the content of naphthalene and / or its derivatives is 0.1 to 100 wt%.

[0019] The temperature of the contact reaction is 200°C to 600°C; and / or, the pressure of the contact reaction is 2 to 10.0 MPa; and / or, the molecular ratio of hydrogen to hydrocarbon is 1 to 20; and / or, the weight space velocity of the heavy aromatic raw material is 1 to 7 h -1 .

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The composite catalyst bed of the present invention can be used for the lightweighting of heavy aromatic hydrocarbons, especially for C9+ A. Lightweighting of aromatics, wherein different pore size molecular sieves are used to match different raw material molecular conversion reactions, which can effectively utilize naphthalene and / or its derivatives in heavy aromatics, improve the utilization rate of heavy aromatic resources, and greatly improve the conversion rate of heavy aromatics lightening reaction and the selectivity of the target product BTX. Specifically, it has a high total conversion rate, a high conversion rate of naphthalene and / or its derivatives, and a high BTX selectivity. DETAILED DESCRIPTION

[0022] One of the purposes of the present invention is to provide a composite catalyst bed, which includes multiple layers of beds filled with catalysts, wherein the catalysts independently include silica-alumina molecular sieves, metal components and optional binders, and the pore structure of the silica-alumina molecular sieves in each bed catalyst gradually decreases in the order of contact with the material.

[0023] In a preferred embodiment, the number of T atoms in the largest ring structure of the silica-alumina molecular sieve in each bed catalyst gradually decreases (preferably in the range of 20 to 6, more preferably in the range of 18 to 9) according to the order of contact with the material.

[0024] The pore sizes of the silicon-aluminum molecular sieves in different beds are different. The "number of T atoms in the skeleton of the largest ring structure" refers to the total number of silicon and aluminum on the skeleton of the largest ring structure.

[0025] In a further preferred embodiment, the silicon-aluminum molecular sieve is selected from at least one of AET molecular sieve, ETR molecular sieve, ZEO-1 molecular sieve, UTD-1F molecular sieve, β zeolite molecular sieve, mordenite molecular sieve, ZSM-12 molecular sieve, Y molecular sieve, MCM-22 molecular sieve, ITQ-1 molecular sieve, ITQ-24 molecular sieve, ITQ-32 molecular sieve, AFR molecular sieve, ZSM-22 molecular sieve, ZSM-23 molecular sieve, ZSM-5 molecular sieve, EU-1 molecular sieve, ITQ-13 molecular sieve, NU-87 molecular sieve, ZSM-34 molecular sieve, and ZSM-11 molecular sieve.

[0026] In a further preferred embodiment, the silicon-aluminum molecular sieve is at least one selected from AET molecular sieve, β zeolite molecular sieve, mordenite molecular sieve, ZSM-5 molecular sieve, ZSM-11 molecular sieve, and ZSM-22 molecular sieve.

[0027] In a preferred embodiment, the aluminum content and / or acid content of the silica-alumina molecular sieve in the catalyst of each bed gradually increases according to the order of contact with the material.

[0028] Among them, there are differences in the number of acidic sites on the silica-alumina molecular sieves between different beds.

[0029] In a further preferred embodiment, the aluminum content and / or acid amount of the silica-alumina molecular sieve in each bed catalyst is 10 to 500 μmol pydg in the order of contact with the material. -1 (Preferably 20 to 450 μmol pydg -1 ) range gradually increases.

[0030] In a further preferred embodiment, the aluminum content and / or acid amount of the silica-alumina molecular sieve in each bed catalyst is 50 to 500 μmol pydg -1 (Preferably 80 to 450 μmol pydg -1 ) range gradually increases.

[0031] In a preferred embodiment, the composite catalyst bed comprises three or more beds filled with catalyst, preferably 3 to 10 layers, more preferably 3 to 6 layers, for example 3, 4, 5, 6, 7, 8, 9 or 10 layers.

[0032] In a preferred embodiment, the composite catalyst bed comprises three layers. In the order of contact with the material, the number of T atoms in the largest ring structure of the silica-alumina molecular sieve in the catalyst of the first bed layer is 14 to 18 (for example, 14, 15, 16, 17 or 18); and / or the number of T atoms in the largest ring structure of the silica-alumina molecular sieve in the catalyst of the second bed layer is 11 to 12 (11 or 12); and / or the number of T atoms in the largest ring structure of the silica-alumina molecular sieve in the catalyst of the third bed layer is 9 to 10 (9 or 10).

[0033] In a further preferred embodiment, the composite catalyst bed comprises three layers. In the order of contact with the material, the silicon-aluminum molecular sieve in the catalyst of the first bed layer is selected from at least one of AET molecular sieve, ETR molecular sieve, ZEO-1 molecular sieve, and UTD-1F molecular sieve; and / or, the silicon-aluminum molecular sieve in the catalyst of the second bed layer is selected from at least one of β zeolite molecular sieve, mordenite molecular sieve, ZSM-12 molecular sieve, Y molecular sieve, MCM-22 molecular sieve, ITQ-1 molecular sieve, ITQ-24 molecular sieve, ITQ-32 molecular sieve, and AFR molecular sieve; and / or, the silicon-aluminum molecular sieve in the catalyst of the third bed layer is selected from at least one of ZSM-22 molecular sieve, ZSM-23 molecular sieve, ZSM-5 molecular sieve, EU-1 molecular sieve, ITQ-13 molecular sieve, NU-87 molecular sieve, ZSM-34 molecular sieve, and ZSM-11 molecular sieve.

[0034] In a further preferred embodiment, the composite catalyst bed comprises three layers. In order of contact with the material, the silicon-aluminum molecules in the catalyst of the first bed layer are screened from AET molecular sieve; and / or, the silicon-aluminum molecules in the catalyst of the second bed layer are screened from at least one of β zeolite molecular sieve and mordenite molecular sieve; and / or, the silicon-aluminum molecules in the catalyst of the third bed layer are screened from at least one of ZSM-5 molecular sieve, ZSM-11 molecular sieve, and ZSM-22 molecular sieve.

[0035] In a preferred embodiment, the composite catalyst bed comprises three layers. In the order of contact with the material, the acid content of the silica-alumina molecular sieve in the catalyst of the first bed is 20 to 200 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the second bed is 200 to 300 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the third bed is 320 to 450 μmol pydg -1 .

[0036] For example, the composite catalyst bed comprises three layers, and the acid amount of the silica-alumina molecular sieve in the catalyst of the first bed layer is 20, 50, 80, 100, 120, 150, 180 or 200 μmol pydg in accordance with the order of contact with the material. -1 and / or, the acid amount of the silica-alumina molecular sieve in the catalyst of the second bed is 200, 220, 240, 260, 280 or 300 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the third bed layer is 320, 340, 360, 380, 400, 420, 440 or 450 μmol pydg -1 .

[0037] In a further preferred embodiment, the composite catalyst bed comprises three layers. In the order of contact with the material, the acid content of the silica-alumina molecular sieve in the catalyst of the first bed is 80-150 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the second bed is 220 to 280 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the third bed is 340 to 400 μmol pydg -1 .

[0038] In a preferred embodiment, the composite catalyst bed comprises three layers, and in the order of contact with the material, the weight ratio of the first bed layer, the second bed layer, and the third bed layer is 1:(1-30):(1-30).

[0039] For example, in the order of contact with the material, the weight ratio of the first bed layer, the second bed layer, and the third bed layer is 1:(1, 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28 or 30):(1, 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28 or 30).

[0040] In a preferred embodiment, the metal components in the catalyst of each bed are independently selected from at least one of Group IB, Group IIB, Group VIB, Group VIII and Group VIIB elements.

[0041] In a further preferred embodiment, the metal components in each bed catalyst are independently selected from at least one of Ni, Mo, Re, Pd, Co, Rh, Ru, Ir, Cr, Pt, and Zn.

[0042] In a preferred embodiment, the loading amount of the metal component in each bed catalyst is independently 0.01 to 25 wt%, wherein the metal loading amount is calculated as the weight of the metal element based on 100 wt% of the total amount of the catalyst.

[0043] For example, the loading amount of the metal component in each bed catalyst is independently 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 22wt% or 25wt%, wherein the metal loading amount is calculated as the weight of the metal element based on 100wt% of the total amount of the catalyst.

[0044] In a further preferred embodiment, the metal loading on each catalyst bed is independently 0.05-10 wt%, wherein the total amount of each catalyst bed is 100 wt%, and the metal loading is calculated as the weight of the metal element.

[0045] In a preferred embodiment, the binder is selected from at least one of alumina, alumina sol, pseudo-boehmite, and silica sol.

[0046] In a preferred embodiment, in each bed of catalyst, based on the total weight of the silica-alumina molecular sieve and the binder as 100 wt%, the silica-alumina molecular sieves are each independently 10-85 wt%, and the binders are each independently 5-80 wt%.

[0047] For example, in the catalyst of each bed layer, based on the total weight of the silica-alumina molecular sieve and the binder as 100wt%, the silica-alumina molecular sieve is independently 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 85wt%, and the binder is independently 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%.

[0048] In a further preferred embodiment, in each bed of catalyst, based on the total weight of the silica-alumina molecular sieve and the binder as 100 wt%, the silica-alumina molecular sieves are each independently 30-80 wt%, and the binders are each independently 20-60 wt%.

[0049] In a preferred embodiment, the composite catalyst bed includes, in sequence along the material flow direction, a first bed filled with a first catalyst, a second bed filled with a second catalyst, and a third bed filled with a third catalyst, and the first catalyst, the second catalyst, and the third catalyst each independently include a silicon-aluminum molecular sieve, the metal component, and optionally the binder.

[0050] In a further preferred embodiment, along the material flow direction from the first catalyst to the third catalyst, the number of skeleton T atoms of the largest ring structure on the silica-alumina molecular sieve gradually decreases, and / or the aluminum content and / or acid content of the silica-alumina molecular sieve gradually increases.

[0051] Thus, the catalyst in the first bed layer is the first catalyst, the catalyst in the second bed layer is the second catalyst, and the catalyst in the third bed layer is the third catalyst.

[0052] In a preferred embodiment, the catalyst of each bed layer is independently prepared as follows: the silica-alumina molecular sieve and the optional binder are mixed to obtain a carrier, the metal component is loaded, and the carrier is molded, dried, and calcined to obtain the catalyst.

[0053] In a further preferred embodiment, the metal component is loaded on the carrier by at least one of metal exchange, adsorption, deposition and impregnation.

[0054] The second object of the present invention is to provide an application of the composite catalyst bed described in the first object of the present invention in the lightening of heavy aromatic hydrocarbons, for example, increasing the production of heavy aromatic hydrocarbons into light C6-C8 aromatic hydrocarbons.

[0055] Wherein, the heavy aromatic hydrocarbons are C9 + A aromatic hydrocarbon.

[0056] The third object of the present invention is to provide a method for lightening heavy aromatic hydrocarbons, comprising: under hydrogen conditions, the heavy aromatic hydrocarbon raw material is contacted and reacted with the composite catalyst bed described in one of the objects of the present invention.

[0057] In a preferred embodiment, the heavy aromatic hydrocarbon feedstock is C9 + A aromatic hydrocarbon, preferably, wherein the content of naphthalene and / or its derivatives is 0.1-100wt%, for example, 0.1wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or 100wt%.

[0058] In a preferred embodiment, the temperature of the contact reaction is 200°C to 600°C; and / or, the pressure of the contact reaction is 2 to 10.0 MPa; and / or, the hydrogen-to-hydrocarbon molecular ratio is 1 to 20.

[0059] For example, the temperature of the contact reaction is 200°C, 300°C, 400°C, 500°C or 600°C; and / or the pressure of the contact reaction is 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa or 10MPa; and / or the hydrogen-to-hydrocarbon molecular ratio is 1, 2, 5, 8, 10, 12, 15, 18 or 20.

[0060] In a preferred embodiment, the weight space velocity of the heavy aromatic feedstock is 1 to 7 h -1 , for example, 1h -1 , 2h -1 , 3h -1 , 4h -1 , 5h -1 , 6h -1 or 7h -1 .

[0061] The third object of the present invention is to overcome the shortcomings of the existing transalkylation technology that cannot effectively process heavy aromatic components containing naphthalene and / or its derivatives. + A method for lightening heavy aromatics. The catalyst system used in the method utilizes molecular sieves of different pore sizes to match different raw material molecules for conversion reactions, which can effectively utilize naphthalene and / or its derivatives in heavy aromatics and improve the utilization rate of heavy aromatics resources.

[0062] The technical scheme adopted by the present invention is as follows: heavy aromatic hydrocarbons containing naphthalene are increased to produce light C6-C8 aromatic hydrocarbons. In a silicon-aluminum molecular sieve catalyst composite bed system with different metal loads, heavy aromatic hydrocarbons containing naphthalene and / or its derivatives of carbon nine and above are used as raw materials, and C6-C8 light aromatic hydrocarbon products rich in benzene, toluene, xylene, etc. are generated under hydrogen conditions. The above-mentioned technical problems are well solved, and the present invention can be applied to the industrial production of lightening of heavy aromatic hydrocarbons containing naphthalene to increase the production of light C6-C8 aromatic hydrocarbons.

[0063] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0064] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0065] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0066] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0067] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0068] The metal loading in Table 1 is a theoretical value deduced from the raw material dosage. Since the initial impregnation method is used, almost all the metal component raw materials are loaded on the catalyst, so the theoretical dosage is almost equal to its actual content.

[0069] [Example 1] Preparation of a catalyst that first contacts a material

[0070] Preparation of the catalyst in the first bed layer: 60 g of hydrogen-type molecular sieve ZEO-1, 40 g of pseudo-boehmite and 3 g of Tianqing powder were evenly mixed, and a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid were added to load the metal components by the initial wetness impregnation method. The catalyst A1 was obtained by extrusion molding, drying and calcining at 500°C for 3 hours.

[0071] Preparation of the catalyst in the first bed layer: 60 g of hydrogen-type molecular sieve ZEO-1, 40 g of pseudo-boehmite and 3 g of appropriate amount of Tianqing powder were mixed evenly, and a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid were added to load the metal components by the initial wet impregnation method, and the catalyst A2 was obtained by extrusion molding, drying and calcining at 500°C for 3 hours.

[0072] Preparation of the catalyst in the first bed layer: 60 g of hydrogen-type molecular sieve UTD-1F, 40 g of pseudo-boehmite and 3 g of Tianqing powder were mixed evenly, and a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid were added to load the metal components by the initial wet impregnation method. The catalyst A3 was obtained by extrusion, drying and calcination at 500°C for 3 hours.

[0073] Preparation of the catalyst in the first bed layer: 60 g of hydrogen-type molecular sieve ETR, 40 g of pseudo-boehmite and 3 g of Tianqing powder were mixed evenly, and a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid were added to load the metal components by the initial wet impregnation method. The catalyst A4 was obtained by extrusion, drying and calcination at 500°C for 3 hours.

[0074] The composition of each catalyst is shown in Table 1.

[0075] [Example 2] Preparation of a catalyst for secondary contact with a material

[0076] Preparation of the catalyst in the second bed layer: Mix 60 grams of hydrogen-type molecular sieve β zeolite, 40 grams of pseudo-boehmite and 3 grams of Tianqing powder evenly, add a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid, use the initial wetness impregnation method to load the metal component, extrude into strips, dry, and calcine at 500°C for 3 hours to obtain catalyst B1.

[0077] Preparation of the catalyst in the second bed layer: Mix 60 grams of hydrogen-type molecular sieve silk zeolite with 40 grams of pseudo-boehmite and 3 grams of Tianqing powder, add a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid, use the initial wet impregnation method to load the metal component, extrude into strips, dry, and calcine at 500°C for 3 hours to obtain catalyst B2.

[0078] Preparation of the catalyst in the second bed layer: Mix 60 grams of hydrogen-type molecular sieve β zeolite, 40 grams of pseudo-boehmite and 3 grams of Tianqing powder evenly, add a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid, use the initial wetness impregnation method to load the metal component, extrude into strips, dry, and calcine at 500°C for 3 hours to obtain catalyst B3.

[0079] Preparation of the catalyst in the second bed layer: Mix 60 grams of hydrogen-type molecular sieve ZSM-12, 40 grams of pseudo-boehmite and 3 grams of Tianqing powder evenly, add a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid, use the initial wetness impregnation method to load the metal components, extrude into strips, dry, and calcine at 500°C for 3 hours to obtain catalyst B4.

[0080] The composition of each catalyst is shown in Table 1.

[0081] [Example 3] Preparation of the catalyst that contacts the material last

[0082] Preparation of the catalyst in the third bed layer: 60 g of hydrogen-type molecular sieve ZSM-5, 40 g of pseudo-boehmite and 3 g of Tianqing powder were evenly mixed, and a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid were added to load the metal components by the initial wet impregnation method. The catalyst C1 was extruded, dried, and calcined at 500°C for 3 hours.

[0083] Preparation of the catalyst in the third bed layer: 60 grams of hydrogen-type molecular sieve ZSM-11, 40 grams of pseudo-boehmite and 3 grams of Tianqing powder were mixed evenly, and a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid were added to load the metal components by the initial wet impregnation method. The catalyst C2 was obtained by extrusion molding, drying and calcining at 500°C for 3 hours.

[0084] Preparation of the catalyst in the third bed layer: 60 grams of hydrogen-type molecular sieve ZSM-11, 40 grams of pseudo-boehmite and 3 grams of Tianqing powder were mixed evenly, and a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid were added to load the metal components by the initial wet impregnation method. The catalyst C3 was obtained by extrusion, drying and calcination at 500°C for 3 hours.

[0085] Preparation of the catalyst in the third bed layer: 60 grams of hydrogen-type molecular sieve ZSM-22, 40 grams of pseudo-boehmite and 3 grams of Tianqing powder were mixed evenly, and a certain amount of metal salt aqueous solution and 5 ml of 60% dilute nitric acid were added to load the metal components by the initial wet impregnation method. The catalyst C4 was extruded, dried, and calcined at 500°C for 3 hours to obtain the catalyst C4.

[0086] The composition of each catalyst is shown in Table 1.

[0087] Table 1: Catalyst number, preparation and composition

[0088]

[0089] [Example 4]

[0090] The composite bed layer I includes three layers, which are the first bed layer, the second bed layer and the third bed layer in the order of contact with the material. The first bed layer is filled with catalyst A1, the second bed layer is filled with catalyst B1, and the third bed layer is filled with catalyst C1.

[0091] [Example 5]

[0092] The composite bed II includes three layers, which are the first bed layer, the second bed layer and the third bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst A2, the second bed layer is filled with catalyst B2, and the third bed layer is filled with catalyst C2. The total loading weight of the three layers is the same as the total loading weight of the three layers in Example 4.

[0093] [Example 6]

[0094] The composite bed III includes three layers, which are the first bed layer, the second bed layer and the third bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst A3, the second bed layer is filled with catalyst B3, and the third bed layer is filled with catalyst C3. The total loading weight of the three layers is the same as the total loading weight of the three layers in Example 4.

[0095] [Example 7]

[0096] The composite bed IV includes three layers, which are the first bed layer, the second bed layer and the third bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst A4, the second bed layer is filled with catalyst B4, and the third bed layer is filled with catalyst C4. The total loading weight of the three layers is the same as the total loading weight of the three layers in Example 4.

[0097] [Example 8]

[0098] The composite bed layer V includes three layers, which are the first bed layer, the second bed layer and the third bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst A1, the second bed layer is filled with catalyst B2, and the third bed layer is filled with catalyst C3. The total loading weight of the three layers is the same as the total loading weight of the three layers in Example 4.

[0099] [Example 9]

[0100] The composite bed layer VI includes three layers, which are the first bed layer, the second bed layer and the third bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst A3, the second bed layer is filled with catalyst B4, and the third bed layer is filled with catalyst C2. The total loading weight of the three layers is the same as the total loading weight of the three layers in Example 4.

[0101] [Example 10]

[0102] The composite bed layer VII includes three layers, which are the first bed layer, the second bed layer and the third bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst A4, the second bed layer is filled with catalyst B1, and the third bed layer is filled with catalyst C1. The total loading weight of the three layers is the same as the total loading weight of the three layers in Example 4.

[0103] [Comparative Example 1]

[0104] The composite bed layer i has only one layer, which is a mixture of catalyst A1, catalyst B1, and catalyst C1, and the weight ratio of catalyst A1, catalyst B1, and catalyst C1 is the same as that of Example 4. The total loading weight of one layer is the same as that of three layers in Example 4.

[0105] [Comparative Example 2]

[0106] The composite bed layer ii includes three layers, which are the first bed layer, the second bed layer and the third bed layer in the order of contact with the material. The first bed layer is filled with catalyst C1, the second bed layer is filled with catalyst B1, and the third bed layer is filled with catalyst A1. The total filling weight of the three layers is the same as the total filling weight of the three layers in Example 4.

[0107] [Comparative Example 3]

[0108] The composite bed layer iii includes two layers, which are the first bed layer and the second bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst A1 and the second bed layer is filled with catalyst B1, and the loading weight ratio of the first bed layer catalyst A1 and the second bed layer catalyst B1 is the same as the loading weight ratio of the catalyst A1 bed layer to the catalyst B1 bed layer in Example 4, and the total loading weight of the two layers in Comparative Example 3 is the same as the total loading weight of the three layers in Example 4.

[0109] [Comparative Example 4]

[0110] The composite bed layer iv includes two layers, which are the first bed layer and the second bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst B1 and the second bed layer is filled with catalyst C1, and the loading weight ratio of the first bed layer catalyst B1 and the second bed layer catalyst C1 is the same as the loading weight ratio of the catalyst B1 bed layer to the catalyst C1 bed layer in Example 4, and the total loading weight of the two layers in Comparative Example 4 is the same as the total loading weight of the three layers in Example 4.

[0111] [Comparative Example 5]

[0112] The composite bed v includes two layers, which are the first bed layer and the second bed layer in the order of contact with the material, wherein the first bed layer is filled with catalyst A1 and the second bed layer is filled with catalyst C1, and the loading weight ratio of the first bed layer catalyst A1 and the second bed layer catalyst C1 is the same as the loading weight ratio of the catalyst A1 bed layer to the catalyst C1 bed layer in Example 4, and the total loading weight of the two layers in Comparative Example 5 is the same as the total loading weight of the three layers in Example 4.

[0113]

Evaluation experiment

[0114] The beds of Examples 4 to 10 and the comparative example were used to lighten heavy aromatic feedstock containing naphthalene and / or its derivatives. The feedstock was contacted with the first layer (first bed layer), the second layer (second bed layer) and the third layer (third bed layer) in sequence. The evaluation conditions and results are shown in Table 2.

[0115] Table 2:

[0116]

[0117] After bed recombination, the conversion rate of heavy aromatics and naphthalene series under the same reaction conditions was improved. Through iv comparison, it was found that after bed recombination, the conversion rate of heavy aromatics, especially naphthalene series, and the selectivity of the target product BTX were greatly improved.

[0118] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A composite catalyst bed, comprising multiple layers of beds filled with catalysts, wherein the catalysts independently comprise a silica-alumina molecular sieve, a metal component and an optional binder, and the pore structure of the silica-alumina molecular sieve in each bed catalyst gradually decreases in the order of contact with the material.

2. The composite catalyst bed according to claim 1, characterized in that: The binder is selected from at least one of alumina, aluminum sol, pseudo-boehmite, and silica sol. Preferably, in each bed of the catalyst, based on the total weight of the silica-alumina molecular sieve and the binder as 100wt%, the silica-alumina molecular sieve is independently 10-85wt%, and the binder is independently 5-80wt%.

3. The composite catalyst bed according to claim 1, characterized in that: The metal components are each independently selected from at least one of Group IB, Group IIB, Group VIB, Group VIII and Group VIIB elements, preferably at least one of Ni, Mo, Re, Pd, Co, Rh, Ru, Ir, Cr, Pt and Zn. More preferably, the loading amount of the metal components in each bed catalyst is each independently 0.01 to 25 wt%.

4. The composite catalyst bed according to claim 1, characterized in that: According to the order of contact with the material, the number of T atoms in the skeleton of the largest ring structure on the silica-alumina molecular sieve in each bed catalyst gradually decreases (preferably in the range of 20 to 6, more preferably in the range of 18 to 9); More preferably, the silicon-aluminum molecular sieve is selected from at least one of AET molecular sieve, ETR molecular sieve, ZEO-1 molecular sieve, UTD-1F molecular sieve, β zeolite molecular sieve, mordenite molecular sieve, ZSM-12 molecular sieve, Y molecular sieve, MCM-22 molecular sieve, ITQ-1 molecular sieve, ITQ-24 molecular sieve, ITQ-32 molecular sieve, AFR molecular sieve, ZSM-22 molecular sieve, ZSM-23 molecular sieve, ZSM-5 molecular sieve, EU-1 molecular sieve, ITQ-13 molecular sieve, NU-87 molecular sieve, ZSM-34 molecular sieve and ZSM-11 molecular sieve.

5. The composite catalyst bed according to claim 1, characterized in that: According to the order of contact with the material, the aluminum content and / or acid amount of the silica-alumina molecular sieve in the catalyst of each bed layer gradually increases; preferably, the aluminum content and / or acid amount of the silica-alumina molecular sieve in the catalyst of each bed layer is 10 to 500 μmol pydg according to the order of contact with the material. -1 (Preferably 20 to 450 μmol pydg -1 ) range gradually increases.

6. The composite catalyst bed according to claim 1, characterized in that: The composite catalyst bed comprises three or more layers filled with catalyst, preferably 3 to 10 layers, more preferably 3 to 6 layers.

7. The composite catalyst bed according to any one of claims 1 to 5, characterized in that: The composite catalyst bed comprises three layers. In the order of contact with the material, the number of T atoms in the skeleton of the largest ring structure of the silicon-aluminum molecular sieve in the catalyst of the first layer is 14 to 18; and / or, the number of T atoms in the skeleton of the largest ring structure of the silicon-aluminum molecular sieve in the catalyst of the second layer is 11 to 12; and / or, the number of T atoms in the skeleton of the largest ring structure of the silicon-aluminum molecular sieve in the catalyst of the third layer is 9 to 10.

8. The composite catalyst bed according to claim 7, characterized in that: The composite catalyst bed comprises three layers. In the order of contact with the material, the silicon-aluminum molecules in the catalyst of the first bed are selected from at least one of AET molecular sieve, ETR molecular sieve, ZEO-1 molecular sieve, and UTD-1F molecular sieve; and / or, the silicon-aluminum molecules in the catalyst of the second bed are selected from at least one of β zeolite molecular sieve, mordenite molecular sieve, ZSM-12 molecular sieve, Y molecular sieve, MCM-22 molecular sieve, ITQ-1 molecular sieve, ITQ-24 molecular sieve, ITQ-32 molecular sieve, and AFR molecular sieve; and / or, the silicon-aluminum molecules in the catalyst of the third bed are selected from at least one of ZSM-22 molecular sieve, ZSM-23 molecular sieve, ZSM-5 molecular sieve, EU-1 molecular sieve, ITQ-13 molecular sieve, NU-87 molecular sieve, ZSM-34 molecular sieve, and ZSM-11 molecular sieve.

9. The composite catalyst bed according to claim 7, characterized in that: The composite catalyst bed comprises three layers. According to the order of contact with the material, the acid content of the silica-alumina molecular sieve in the catalyst of the first bed is 20-200 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the second bed is 200 to 300 μmol pydg -1 and / or, the acid content of the silica-alumina molecular sieve in the catalyst of the third bed is 320 to 450 μmol pydg -1 .

10. The use of the composite catalyst bed according to any one of claims 1 to 9, preferably in the lightening of heavy aromatic hydrocarbons.

11. A method for lightening heavy aromatics, comprising: Under hydrogenation conditions, the heavy aromatic hydrocarbon feedstock is contacted and reacted with the composite catalyst bed according to any one of claims 1 to 9.

12. The method for lightening heavy aromatics according to claim 10, characterized in that: The heavy aromatic hydrocarbon raw material is C9 + A aromatic hydrocarbon, preferably, wherein the content of naphthalene and / or its derivatives is 0.1 to 100 wt%; Preferably, The temperature of the contact reaction is 200°C to 600°C; and / or, the pressure of the contact reaction is 2 to 10.0 MPa; and / or, the molecular ratio of hydrogen to hydrocarbon is 1 to 20; and / or, the weight space velocity of the heavy aromatic raw material is 1 to 7 h -1 .

Citation Information

Patent Citations

  • Heavy Aromatics Conversion Processes and Catalyst Compositions Used Therein

    US20200031740A1

  • Method of heavy reformate conversion into BTX over metal-impregnated ZSM-5+nanocrystalline beta zeolite composite catalyst; said composite catalyst

    WO2019177961A1

  • Methylbenzene and heavy aromatics disproportionating and transalkylation method

    CN104557418A

  • Composite catalyst and method of modifying Fischer-Tropsch wax to produce lubricant base oil

    CN109701590A

  • Combined process for transalkylation of benzene and heavy aromatics and methylation of toluene

    CN114426456A